THE RELATIONSHIP BETWEEN INNOVATIVENESS AND EXPORT IN CROATIAN COMPANIES - Helena Šlogar; Heri Bezić (Poslovna Izvrsnost, 2019)
The purpose of this paper is to examine the relationship between innovativeness and export in Croatian companies. The study involved 303 Croatian export companies from the manufacturing industry and the information and communication technology sector. The survey was conducted using the survey method over the last three months of 2016. For this purpose, Spearman rank correlation, the Kruskal-Wallis ANOVA test and canonical analysis were used. The results show that there is a positive relationship between innovativeness and export in Croatian companies. The results offer theoretical and managerial implications. This research has practical implications for Croatian companies to increase their efficiency and innovativeness. Value is reflected in the relationship between innovativeness and export and there is an important research gap in the literature on international trade, entrepreneurship and management. In the context of this research, it is likely that innovativeness influences a company's export activities, which can be positively reflected in creating and maintaining their competitive advantage on the international market.